LANJUT USIA DALAM KARYA SENI GRAFIS - Agriansyah Agriansyah; Irwan Irwan (Universitas Negeri Padang, 2020)
Old age can result in a decline in physical, psychological, economic and social life. A decrease in these conditions can cause the elderly to experience several problems in their lives. This final work aims to visualize various life and old age problems as a concept of graphic artwork. Showing a variety of old life atmosphere and various problems, which are largely ignored in social life.The method in creating this work uses a high print technique with a reduction print coloring technique. The process of work used in the creation of graphic art works goes through several stages, namely preparation, elaboration, synthesis, concept realization, and completion stages.The results of the visualization of old life in this graphic work in the form of 10 works with the title: (1) Forgotten, (2) The most beautiful memories, (3) There is no choice, (4) Travel, (5) Limited, (6) Hope, ( 7) Interaction, (8) Happiness, (9) Unbearable longing, (10) StruggleKata kunci: lanjut usia, kehidupan sosial, seni grafis